Trigger factors of cutaneous lupus erythematosus: a review of current literature. (July 2017) - Szczęch, J; Samotij, D; Werth, V P; Reich, A
It is currently believed that autoimmune conditions are triggered and aggravated by a variety of environmental factors such as cigarette smoking, infections, ultraviolet light or chemicals, as well as certain medications and vaccines in genetically susceptible individuals. Recent scientific data have suggested a relevant role of these factors not only in systemic lupus erythematosus, but also in cutaneous lupus erythematosus (CLE). A variety of environmental factors have been proposed as initiators and exacerbators of this disease. In this review we focused on those with the most convincing evidence, emphasizing the role of drugs in CLE. Using a combined search strategy of the MEDLINE and CINAHL databases the following trigger factors and/or exacerbators of CLE have been identified and described: drugs, smoking, neoplasms, ultraviolet radiation and radiotherapy. In order to give a practical insight we emphasized the role of drugs from various groups and classes in CLE. We also aimed to present a short clinical profile of patients with lesions induced by various drug classes.